The Mediating Role of Shopping Lifestyle in the Effect of Financial Literacy and PayLater Usage on Impulsive Buying among Civil Servants - Marna Marthen Rando; Lailani Silmina Kresida; Nurun Nida Nilhar; Rahmawati Rahmawati; Syarifah Hudayah; Sugeng Hariyadi (Poltanesa, 2026)
This study aims to examine the effect of financial literacy and PayLater usage on impulsive buying, with shopping lifestyle as a mediating variable among civil servants in Samarinda City. The rapid growth of Buy Now Pay Later services has changed consumer payment behavior by offering instant credit, transaction convenience, and deferred payment options. Although PayLater provides financial flexibility, it may also reduce the psychological pain of paying and increase unplanned purchases. This research applies a quantitative approach using Partial Least Squares-Structural Equation Modeling with 350 civil servants who had used PayLater services within the last six months. The questionnaire consisted of 57 indicators measured using a five-point Likert scale. The findings show that financial literacy has a positive and significant effect on shopping lifestyle, but it does not directly influence impulsive buying. PayLater usage significantly affects both shopping lifestyle and impulsive buying. Shopping lifestyle also significantly influences impulsive buying and mediates the effects of financial literacy and PayLater usage. These findings indicate that impulsive buying is driven more strongly by shopping lifestyle and digital payment convenience than by financial knowledge alone.